Comparison analysis on the bilateral efforts of farmers and the third-party organization under multiple contract modes. Issue 5 (7th May 2019) - Sun, Lanying; Li, Xiaoyan
Abstract : Purpose: The purpose of this paper is under the analysis framework of the system theory, analyzing the optimal contract mode of agricultural supply chain to guarantee the stability of agricultural supply chain and the equilibrium of agricultural product market, to analyze the effect of farmers' risk attitude on the selection of contract modes and to find the way to encourage farmers' productive effort and to avoid farmers' hitchhiking behavior, to guarantee the stability of agricultural supply chain. Design/methodology/approach: Under the guidance of the system theory, using the Stackelberg model and the nonlinear programming theory, this paper comparatively analyzes farmers' effort (productive effort and sales effort), farmers' income and the stability of agricultural supply system of four types of contract modes between farmers, third-party organizations and market. Findings: First, in the agricultural market, market-type contract cannot maximize farmers' income. The main reason is that farmers do not have enough ability to avoid market risk and to bargain. Second, for farmers of risk seeking, choosing a market-type contract and secondary-income contract can increase their income. Third, under the fixed-purchase price contract, the hitchhiking behavior would happen. Fourth, when farmers' productive efforts are the same, farmers' income under the secondary-income contract is higher than under the fixed-purchase price contract. Because under the secondary-income contract, farmers have the opportunity to obtain the secondary distribution of benefits, farmers' hitchhiking behavior could be avoided. Originality/value: Analyzing the contract modes between farmers and the third-party organization in the agricultural market could reduce the influence of price fluctuation, avoid the uncertainty of the relationship between the supply and demand, stimulate the productive effort of farmers and provide theoretical guidance for establishing efficient and stable agricultural supply system.